The Level of Career Involvement of Primary School Managers in Baghdad (Journal of the College of Education for Women, 2018)
The study aimed to identify career engagement among school principals, the researcher used descriptive approach and reached the study sample (230) school, principals. The researcher instruments used: career engagement, has been checked and face validity, and construction and consistency of the instruments using internal consistency Cronbach's alpha The study came to the following findings: - The degree of career engagement among school principals was (29.0200) this refers to a higher level, compared with the theoretical average of (27) and the study showed that the results showed no significant statistical differences between school principals in the level of career engagement due to the variable sex.